A New Era of Religious Freedom: Uzbekistan’s Religious Reforms under President Mirziyoyev (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
Over the past eight years, Uzbekistan has implemented gradual reforms in its religious policies, focusing on promoting a more moderate interpretation of Islam and revitalizing religious practices. This article explores the key changes in religious life under the leadership of President Shavkat Mirziyoyev, emphasizing legal reforms, the expansion of religious education, and the government’s evolving approach to Islam. The paper also examines the broader implications of these changes, including their impact on Uzbek society, interfaith relations, and the state's efforts to balance religious freedom with the prevention of extremism.